Impact of COVID-19 on Sexually Transmitted Infection Burden: A Cross-Sectional Study from a Tertiary Care Hospital in Gujarat - Patel, Sonal; Thakkar, Sejal; Sangam, Vimal; Shah, Mudra (Journal of Neonatal Surgery, 2025)
Background:Chronic Spontaneous Urticaria (CSU) is a persistent skin disorder characterized by recurrent wheals, angioedema, or both, lasting for at least six weeks without an identifiable trigger. CSU significantly affects patients’ quality of life, often causing sleep disturbances, emotional distress, and reduced work productivity. First-line treatment involves second-generation H1-antihistamines, but many patients remain refractory to standard doses, necessitating dose escalation or antihistamine switching. Objective:This study aims to evaluate the efficacy of three second-generation antihistamines—Fexofenadine, Levocetirizine, and Desloratadine—in CSU management, focusing on symptom relief, dose escalation, antihistamine switching, and adverse effects. Methods:A prospective, observational study was conducted on 300 CSU patients at a dermatology outpatient clinic. Patients were initially treated with standard doses of Levocetirizine (5 mg), Desloratadine (5 mg), or Fexofenadine (180 mg). Non-responders underwent a stepwise dose escalation up to fourfold. Patients who remained symptomatic despite escalation were switched to a different antihistamine. Symptom severity was assessed using the Urticaria Activity Score (UAS), and adverse effects were monitored over a six-month follow-up period. Results:Fexofenadine demonstrated superior efficacy, with 87% of patients achieving symptom relief after fourfold dose escalation, compared to 38% with Levocetirizine and 15% with Desloratadine. Antihistamine switching yielded a 31.5% response rate among non-responders, with the highest success observed when switching from Desloratadine to Levocetirizine (18.5%). Fexofenadine showed the greatest reduction in UAS at one-week (50%) and three-week (75%) follow-ups (p<0.05). Adverse effects were minimal, with headaches more common in the Fexofenadine group, while drowsiness was prevalent in Levocetirizine and Desloratadine groups. Conclusion:Fexofenadine is the most effective antihistamine for CSU management, particularly at higher doses. Dose escalation significantly improves symptom control, while antihistamine switching benefits a subset of non-responders. Personalized treatment strategies considering patient-specific responses can enhance clinical outcomes in CSU. Future research should focus on biomarker-based therapy and combination treatments to optimize CSU management